ANALISIS PENGGUNAAN RAGAM BAHASA GAUL DALAM KONTEN PENDIDIKAN DI TIKTOK : SYSTEMATIC LITERATURE REVIEW (SLR) - Dwi Nuraini, Leny; Azila, Nova; Safarani Jannah, Vidyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the use of slang language in educational content on TikTok through the Systematic Literature Review (SLR) method. Data were collected from various relevant scholarly articles published within the last five years and processed using content analysis techniques. The findings reveal that slang in educational content appears in several forms such as abbreviations, acronyms, and loanwords from foreign languages, which are employed to enhance the appeal and effectiveness of material delivery. The use of slang has been shown to increase learning interest, facilitate comprehension, and create closeness between content creators and audiences. Nevertheless, negative impacts were also identified, including a decline in formal language proficiency and the mixing of language registers. Therefore, slang usage must be managed wisely in educational contexts to ensure it continues to support the quality of the Indonesian language. The role of educators is crucial in guiding students to balance informal and formal language use.